Can anybody translate (y + 3)(y -2)

1 answer

not sure what you mean by "translate"

"the expression y plus 3 is multiplied by the expression y minus 2" ?????

Did you want to expand it? Then...

y^2 - 2y + 3y - 6
= y^2 + y - 6
Similar Questions
    1. answers icon 1 answer
  1. What steps transform the graph of y=x^2 to y=-(x+3)+5a reflect across the x-axis, translate 3 units to the right, translate down
    1. answers icon 1 answer
  2. Which steps transform the graph of y=x^2 to y=-2(x-2)^2+2.a) translate 2 units to the left translate down 2 units stretch by
    1. answers icon 46 answers
  3. Which steps transform the graph of y = x2 to y = –2(x – 2)2 + 2?(1 point) Responses translate 2 units to the left, translate
    1. answers icon 1 answer
more similar questions